Evaluation of Faecalibacterium 16S rDNA genetic markers for accurate identification of swine faecal waste by quantitative PCR. (1st October 2016) - Duan, Chuanren; Cui, Yamin; Zhao, Yi; Zhai, Jun; Zhang, Baoyun; Zhang, Kun; Sun, Da; Chen, Hang
Abstract: A genetic marker within the 16S rRNA gene of Faecalibacterium was identified for use in a quantitative PCR (qPCR) assay to detect swine faecal contamination in water. A total of 146, 038 bacterial sequences were obtained using 454 pyrosequencing. By comparative bioinformatics analysis of Faecalibacterium sequences with those of numerous swine and other animal species, swine-specific Faecalibacterium 16S rRNA gene sequences were identified and Polymerase Chain Okabe (PCR) primer sets designed and tested against faecal DNA samples from swine and non-swine sources. Two PCR primer sets, PFB-1 and PFB-2, showed the highest specificity to swine faecal waste and had no cross-reaction with other animal samples. PFB-1 and PFB-2 amplified 16S rRNA gene sequences from 50 samples of swine with positive ratios of 86 and 90%, respectively. We compared swine-specific Faecalibacterium qPCR assays for the purpose of quantifying the newly identified markers. The quantification limits (LOQs) of PFB-1 and PFB-2 markers in environmental water were 6.5 and 2.9 copies per 100 ml, respectively. Of the swine-associated assays tested, PFB-2 was more sensitive in detecting the swine faecal waste and quantifying the microbial load. Furthermore, the microbial abundance and diversity of the microbiomes of swine and other animal faeces were estimated using operational taxonomic units (OTUs). The species specificity was demonstrated for the microbial populations present in various animal faeces. Graphical abstract: Highlights: This is the first application of Faecalibacterium to detect swine faeces. Abundance and diversity of the microbiome in animal faecal samples were assessed. QPCR assay was developed to evaluate the sensitivity of swine-specific markers. Swine-specific Faecalibacterium markers can help track swine faecal contamination.